2021
DOI: 10.1111/ffe.13516
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and fracture toughness of electron beam welded joints of aluminum alloy 6156 (Al–Mg–Si) for aerospace applications

Abstract: The mechanical behavior of AA6156 electron beam welded joints and the effect of artificial aging heat treatments on the fracture‐related properties were investigated. The fatigue test results of the welded joints presented lower fatigue endurance limit by approximately 60%, when compared to the base material. Fracture resistance results showed that the critical stress intensity factor (Kcr) was essentially decreased (~32%) in the as‐welded condition. Heat treatment before welding presented a 15% increase in Kc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Microhardness increases from the HAZ region towards the BM. It is suggested that a solution annealing treatment should be performed to restore the hardness [36].…”
Section: Microhardness Testmentioning
confidence: 99%
“…Microhardness increases from the HAZ region towards the BM. It is suggested that a solution annealing treatment should be performed to restore the hardness [36].…”
Section: Microhardness Testmentioning
confidence: 99%
“…It can be applied to weld titanium alloys, aluminum alloys, heat-resistant steel and Ni-based alloys, etc. [1][2][3][4][5] Ni-based superalloys, a class of materials having high temperature resistance and oxidation resistance, are widely used in aero engines, gas turbines, and other high-temperature components. 6,7 GH4169 is a grade of Ni-based superalloy from China, and its maximum operating temperature is 650 C, which has the similar microstructure and mechanical properties to Inconel 718.…”
Section: Introductionmentioning
confidence: 99%
“…Electron beam welding (EBW) has been used for the manufacture and maintenance of aero engines for decades due to the excellent performance in dimensional accuracy and welding quality. It can be applied to weld titanium alloys, aluminum alloys, heat‐resistant steel and Ni‐based alloys, etc 1–5 . Ni‐based superalloys, a class of materials having high temperature resistance and oxidation resistance, are widely used in aero engines, gas turbines, and other high‐temperature components 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Low weight and high strength are the main basis for the selection of materials for high‐speed trains. Additionally, 6XXX series Al alloys have been widely used in structural body parts because of their low density, medium strength, good‐forming ability, and excellent welding performance 1–5 . However, fatigue cracks usually occur in the Al alloy components because of the alternating load during long‐term service 6–12 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 6XXX series Al alloys have been widely used in structural body parts because of their low density, medium strength, good-forming ability, and excellent welding performance. [1][2][3][4][5] However, fatigue cracks usually occur in the Al alloy components because of the alternating load during long-term service. [6][7][8][9][10][11][12] It is estimated that 80% to 90% of the engineering component failures may result from a fatigue fracture.…”
Section: Introductionmentioning
confidence: 99%